2011
DOI: 10.7439/ijbr.v2i9.164
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Plants and Propionibacterium Acnes: An Overview

Abstract: Propionibacterium acnes are gram-positive anaerobic microorganism, which have been most recognized as a key factor for the development of acne. Acne is the most common skin disease and Propionibacterium acnes have been recognized as pus-forming bacteria triggering an inflammation in acne. Acne vulgaris is a chronic inflammatory disease of the pilosebaceous follicle, characterized by comedones, papules, pustules, cysts, nodules and often scars in certain sites of predilection, namely, the face, neck, upper trun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Antimicrobial and antiviral effects were demonstrated using a very broad spectrum of plant essential oils (Bassole and Juliani ) and their use in food technology (Burt ), cosmetics (Singh and others ; Dreger and Wielgus ), and medicine, for example to control bacterial infections resistant to conventional antibiotics (Solórzano‐Santos and Miranda‐Novales ; Yap and others ), has been discussed. Unfortunately, most attention has been focused on examining these effects using plant extracts, whose composition is complex and variable, and only a few studies have examined properties of pure substances.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…Antimicrobial and antiviral effects were demonstrated using a very broad spectrum of plant essential oils (Bassole and Juliani ) and their use in food technology (Burt ), cosmetics (Singh and others ; Dreger and Wielgus ), and medicine, for example to control bacterial infections resistant to conventional antibiotics (Solórzano‐Santos and Miranda‐Novales ; Yap and others ), has been discussed. Unfortunately, most attention has been focused on examining these effects using plant extracts, whose composition is complex and variable, and only a few studies have examined properties of pure substances.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…It is, in fact, one of the most prevalent dermatologic diseases in the world and occurs mostly on the face, back and chest . Although not a serious health threat, severe acne can lead to permanent scarring; which makes it a significant clinical condition that may negatively affect a person emotionally, psychologically and even socially . Regardless of the emotional and social implications, it has also become a condition that is less seen as a disease requiring medical attention, and more designated for cosmetic intervention .…”
Section: Introductionmentioning
confidence: 99%
“…Side effects of isotretinoin, the most successful anti‐acne agent, include headaches, nausea, dry skin, joint and muscle pain, depression and suicidal tendencies. The topical antimicrobial treatments are generally the preferred treatment and exert a suppressing effect on the bacterial pathogens involved in acne; however, these are limited in their use due to the development of resistance . This emphasizes the importance of discovering alternative acne treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In view of increasing resistance to existing anti-microbial agents, side effects and sometimes high cost of treatment (Oprika, 2006;Ghosh et al, 2011;Hamburger and Hostettmann, 1991), discovering an effective treatment for acne that is well tolerated by the patients is a challenge. Singh et al (2011) reviewed the possible correlation between antimicrobial activities of medicinal plants against the etiologic agents of acne vulgaris. They found that different parts of various medicinal plants belonging to families like Liliaceae, Rutaceae, Zingiberaceae, Myrtaceae, Lamiaceae, etc contain alkaloids, tannins, flavonoids, terpenoids, volatile oil and essential oil which are reported with significant effect against this bacteria.…”
Section: Introductionmentioning
confidence: 99%